Higher spin symmetries and w∞ algebra in the conformal affine Toda model - Aratyn, H.; Constantinidis, C. P. [UNESP]; Ferreira, L. A. [UNESP]; Gomes, J. F. [UNESP]; Zimerman, A. H. [UNESP] (Elsevier, 1992)
As recently shown the conformal affine Toda models can be obtained via hamiltonian reduction from a two-loop Kac-Moody algebra. In this paper we propose a systematic procedure to analyze the higher spin symmetries of the conformal affine Toda models. The method is based on an explicit construction of infinite towers of extended conformal symmetry generators. Two fundamental building blocks of this construction are special spin-one and -two primary fields characterizing the conformal structure of these models. The connection to the algebra of area preserving diffeomorphisms on a two-manifold (w∞ algebra) is established.